Synthesis & Characterization Of Poly [ N - acryl - N - sulfonic acid - N\ yL - 2 - substituted - 4 - oxo - thiazolidine ] Maleic and Succinic DiImide - Abd Al-Hassan, Hayder M. Amen (Iraqi Journal of Science, 2023)
In the present investigation, new polymers of Poly [ N - acryl - N - sulfonic acid - N\ yL - 2 - substitute - 4 - oxo - thiazolidine ] Maleic and Succinic diimide were synthesized by seven steps; first step includes esterification of different cyclic anhydride, using one mole of absolute methanol in the presence few drops of conc. H2SO4, yielded mono group ester [I] , which was reaction with thionyl chloride to give ester acid chloride [II] .Then reacted with sulfanilic acid to product compound [III] , which was condensation with hydrazine hydrate to give acid hydrazide [IV] . The new different Schiff bases [V-VIII] were synthesized by reaction of acid hydraizide with different (aliphatic and aromatic) aldehyedes and ketones in the presence of glacial acetic acid. Thiazolidine-4-one derivatives [IX-XII] have been obtained from the addition of 2-mercapto acetic acid to Schiff bases and the final step was added poly acryloyl chloride to product polymers [XIII-XVI] . There chemical structures have been confirmed by melting points , FTIR,1HNMR and 13C-NMR (some of them). All the synthesized polymers were characterized by FT– IR spectra, softening points and TGA,DTG (some of them)